Effects of Tolterodine and Tamsulosin Combination on Sypmtoms and Bladder Outlet Obstruction in Patients with Benign Prostate Hyperplasia (Annals of Medical Research, 2021)
Aim: To compare the symptomatic and urodynamic aspects of mono-therapies and combination therapies of tolterodine and tamsulosin.